STUDI DESKRIPTIF PENGARUH LIMBAH INDUSTRI PERIKANAN MUNCAR, BANYUWANGI TERHADAP LINGKUNGAN SEKITAR - Hikamah, Siti Roudlotul; Mubarok, Husni (Pendidikan Biologi,Universitas Islam Jember, 2012)
Waste is a substance, energy or components that could be degrading the environmental quality. Waste (pollutants) may be solid, liquid and gas. Liquid waste in the form of fish oil and some gas or solid waste from fish processing in Muncar, Banyuwangi has positive and negative impacts for the environment. The purpose of this study was to determine the extent of the influence of fish processing wastes on aquatic ecosystems and the economic aspects of communities around the industrial area as well as ways to overcome them. This study uses descriptive research method with interview techniques and field observations in three stages, namely interviews, observation and determination. The independent variable is industrial waste. Dependent variable is the environment surrounding industrial area. There are changes in color, odor and sediment colloids in the waters around the industry. Disease often complained about the plant communities are coughing and itching. For people who were left to waste disposal plants, the waste is very harmful to society, but for the scavengers of fish oil, waste to be very beneficial because it can make money. Profits average of fish oil processing is 52.67%. The way of handling liquid waste pollution is can be making room seepage, selfpurification and the establishment of fish oil processing plant.Key words: waste, industry, fish processing, Muncar, environmental